Is There a Feedback Mechanism in Accounting? - Krzysztof Drachal (European Financial and Accounting Journal, 2014)
The aim of this paper is to present some considerations about the (market) reality and the accounting. The considerations are some kind of a discussion, how accounting systems are linked by the feedback mechanism with managers. Various aspects of modern markets are presented. In particular, the role of globalization processes, increasing role of financial institutions and role of information are discussed. It is argued that the accounting becomes more interdisciplinary topic and some skills from new technologies become a must on modern markets. The discussion is illustrated by some particular examples. It is argued that there is a strong feedback mechanism between managers and accounting information systems.
Keywords: M10; M41; 650; Accounting information system; Accounting standards; Creative accounting; Information in accounting; Objectivity in accounting